PENYULUHAN HUKUM TENTANG HAK PILIH PEMILIH PEMULA BAGI ANAK YANG MENGGUNAKAN HAK POLITIKNYA - Muzayanah Muzayanah (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Community Service Activities are the implementation of the Tri Dharma of Higher Education which must be carried out in order to provide understanding to the community, especially for the